2008
DOI: 10.1371/journal.pone.0002296
|View full text |Cite
|
Sign up to set email alerts
|

Early Neurodegeneration Progresses Independently of Microglial Activation by Heparan Sulfate in the Brain of Mucopolysaccharidosis IIIB Mice

Abstract: BackgroundIn mucopolysaccharidosis type IIIB, a lysosomal storage disease causing early onset mental retardation in children, the production of abnormal oligosaccharidic fragments of heparan sulfate is associated with severe neuropathology and chronic brain inflammation. We addressed causative links between the biochemical, pathological and inflammatory disorders in a mouse model of this disease.Methodology/Principal FindingsIn cell culture, heparan sulfate oligosaccharides activated microglial cells by signal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
145
1
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 125 publications
(167 citation statements)
references
References 51 publications
14
145
1
2
Order By: Relevance
“…This concept was recently supported by the findings of Ausseil et al (6), who demonstrated priming of microglia via the TLR4 pathway in the brains of MPS IIIB mice. In addition to heparan sulfate fragments, gangliosides accumulate in the brains of MPS IIIB mice, and it is possible that gangliosides and/or other storage products in connective tissue cells may also contribute to TLR4 activation.…”
mentioning
confidence: 61%
See 1 more Smart Citation
“…This concept was recently supported by the findings of Ausseil et al (6), who demonstrated priming of microglia via the TLR4 pathway in the brains of MPS IIIB mice. In addition to heparan sulfate fragments, gangliosides accumulate in the brains of MPS IIIB mice, and it is possible that gangliosides and/or other storage products in connective tissue cells may also contribute to TLR4 activation.…”
mentioning
confidence: 61%
“…3F). TNF-α is an important downstream mediator of TLR4, and several investigators have recently shown that TLR4 activation and/or TNF-α has important pathogenic effects in the brains of MPS mouse models (6,25). We therefore examined the locomotor behavior of the DKO mice using an accelerating rotarod (Fig.…”
mentioning
confidence: 99%
“…The associated accumulation of substances like GM3 gangliosides, 21 subunit c of mitochondrial ATP synthase (ScMAS), 22 ubiquitin, or lysozyme 23 is not currently understood. Mechanisms leading to the development of neuroinflammation 24 and loss of synaptophysin expression, 25 which both predominates in the rostral cortex, and neuropathology, which is spread throughout the central nervous system, are also ignored. Neurological manifestations are predominant in children with MPSIIIB, evolving over few years from behavioral changes to profound mental retardation.…”
mentioning
confidence: 99%
“…The role of toll-like receptors (TLR) signaling has been highlighted as one of the major contributors to brain inflammatory responses and microglial cell activation with age and neurodegenerative diseases [31]. Recent findings by Ausseil et al have demonstrated that microglial cell activation could be primed by heparan sulfate oligosaccharides via the TLR4 pathway in the brains of MPS IIIB mice at very early stage of the disease [32]. In addition, it has been reported that changes in ganglioside expression or availability at the plasmalemma may also alter TLR4 signaling pathway and trigger microglial activation [33].…”
Section: Other Pathogenic Signaturesmentioning
confidence: 99%